2020
DOI: 10.1097/ncc.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Tripod Approach for Cancer Patients on Illness Stress, Health-Promoting Lifestyle, Hope, and Resilience

Abstract: Background Health-related exercise and education program for cancer patients are necessary to provide physical and emotional support to enable efficient and appropriate self-management at home. Objective This study aimed to investigate the effects of a tripod approach including physical exercise, education, and emotional support program on illness stress, health promotion lifestyle, hope, and resilience in cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…When the studies conducted by adopting Meleis’s transition theory in patients in a variety of groups was examined in the literature, it was found that the patients received favorable related outcomes (Lai et al, 2019; Sung et al, 2021). In their study, Sung and colleagues (2021) adopted a tripod approach to cancer patients, including physical exercise, training, and moral support, and determined that patients had decreased disease stress and that the intervention had positive effects on health-promoting lifestyle (stress management, medical attitudes, and meaning of life). Although the study groups differ, the effective use of intervention methods as a consequence of the theoretical frameworks built according to Meleis’s theory may be interpreted as the common aspect of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…When the studies conducted by adopting Meleis’s transition theory in patients in a variety of groups was examined in the literature, it was found that the patients received favorable related outcomes (Lai et al, 2019; Sung et al, 2021). In their study, Sung and colleagues (2021) adopted a tripod approach to cancer patients, including physical exercise, training, and moral support, and determined that patients had decreased disease stress and that the intervention had positive effects on health-promoting lifestyle (stress management, medical attitudes, and meaning of life). Although the study groups differ, the effective use of intervention methods as a consequence of the theoretical frameworks built according to Meleis’s theory may be interpreted as the common aspect of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical methods used in studies on health‐promoting lifestyle in existing literature are often variable‐centred approaches (Nelson et al., 2023 ; Tabrizi, 2015 ). It is common practice to evaluate one's level of health‐promoting lifestyle based on the average scores of health‐promoting lifestyle measures with the assumption that study samples come from a homogeneous population (Sung, Yu, et al., 2021 ). On the other hand, the health‐promoting lifestyle is a multidimensional variable with dimensions such as spiritual growth, physical activity, health management, nutrition, and health responsibility, each of which is measured using multiple items (Teng et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Turkey showed that cancer patients with a greater belief in the meaning of life have higher levels of psychological resilience and experience less suffering in life [12]. Another study in Korea suggested that people with cancer seek positive meaning in life by promoting positive emotions and improving their lifestyles, and this gives them hope [13]. The results of a study showed that the meaning of life for cancer patients in Iran induces their personal growth [14].…”
Section: Introductionmentioning
confidence: 99%